Property Improvement of Ordinary Portland Cement by Incorporating with Nanosilica - Gopalakrishnan1, R.; Govindarajan2, D. (Asian Journal of Chemistry, 2013)
Nanotechnology has nowadays a pronounced impact on several areas of science and industry. Among several advantages, nano materials have been reported to introduce improvements in terms of system reliability, extend functionality beyond traditional applications and decrease energy consumption in structures. Nano materials can enable better utilization of natural resources and reaching required materials properties with minimal usage. Nano-cement and nano silica are among the recently used materials in this regard. In this paper the influence of nanosilica particles on the mechanical, physical and chemical properties has been studied through measurement of compressive strength, water absorption and the setting time measurements. The experimental results show that the mortar mixed with nano silica were better than that of plain cement mortar, as well as the water absorption results showed that the nano scale silica particles filled the cement paste pores and by reacting with calcium hydroxide crystals from calcium silicate hydration, decreased the size and amount of these crystals. Therefore the results indicate that nanoscale silica behaves not only as a filler to improve microstructure, but also as an activator to promote pozzolanic reaction.